W.C. Fields Collected Shorts - Fields, W. C. (William Claude), 1880-1946.; Brice, Monte, d. 1962.; Pearce, Leslie; Gray, Arnold; Kane, Babe, 1909-; Granger, Dorothy; Bruckman, Clyde, d. 1955.; Chandler, George, 1898-1985; Cramer, Richard, 1890-1960.; Cavanna, Elise, 1902-1963.; Theby, Rosemary; Platinum Disc Corporation; et al. (La Crosse, WI : Platinum Disc Corp., 2000)
W. C. Fields stars in three comedy films. In "The Golf Specialist" he poses as a golf instructor at a fashionable hotel and gives some hilarious golf lessons to the wife of a jealous house detective. "The Dentist" is about a day in the life of a dentist. In "The Fatal Glass of Beer" Fields' son drinks the fatal glass, goes to jail, then returns.
The Golf Specialist / directed by Monte Brice ; with W.C. Fields. 21 min. 1930 -- The Dentist / directed by Leslie Pearce ; with W.C. Fields, Babe Kane, Arnold Gray, Dorothy Granger, Elise Cavanna, Zedna Farley. 21 min. ; 1932 -- The Fatal Glass of Beer / directed by Clyde Bruckman ; with W.C. Fields, Rosemary Theby, George Chandler, Rychard Cramer. 21 min. ; 1933.
Videodisc release of the 1930, 1932, and 1933 short films.
Special features: Trivia quizzes, biographies.
DVD; Dolby digital.
Keywords: Comedy films; Short films; Feature films